Assessing the Impact of Administrative Reforms on Investment Environment and Economic Development in Vietnam - Thanh Thuy, Phan Thi (VNU Journal of Science: Legal Studies, 2025)
In theory and in many countries' practical experience, administrative reform (AR) has a dialectical relationship with socio-economic development. Recognizing this deep interrelation, since 2001, the Communist Party and the Government of Vietnam have gradually implemented comprehensive and profound administrative reforms. Currently, Vietnam is in the third phase (2021–2030), which encompasses six major areas of reform, focusing on institutional improvement, organizational restructuring, civil service, public finance reforms, and administrative modernization. This study will analyze the impacts of Vietnam's administrative reform on the investment environment and economic development. It also evaluates existing limitations and proposes recommendations for further reforms to foster a healthy investment climate and enhance socio-economic growth in Vietnam.